Design, synthesis and cytotoxic effects of curcumin derivatives on K562, MCF-7 and MDA-MB-231 cancer cell lines - Akhtar, Muhammad Nadeem; Siti Noor Hajar, Zamrus; Yeap, Swee Keong; Noorjahan Banu, Alitheen; Seema, Zareen (2018)
Curcumin is one of the leading compound extracted from the dry powder of Curcuma longa (Zingiberaceae family), which possess several pharmacological properties. However, in vivo administration exhibited limited applications in cancer therapies. Twenty four curcumin derivatives were synthesized, comprising cyclohexanone 1-10, acetone 11-17 and cyclopentanone 18-24 series. All the curcuminoids were synthesized by acid or base catalysed Claisen Schmidt reactions in which the β-diketone moiety of curcumin was modified with mono-ketone. These curcuminoids 1-24 were screened against HeLa, K562, MCF-7 (an estrogen-dependent) and MDA-MB-231 (an estrogen-independent) cancer cell lines. Among them, acetone series 11-17 were found to be more selective and potential cytotoxic agents. Compound 14 exhibited activity (IC50 = 3.02±1.20 and 1.52±0.60) against MCF-7 and MDA-MB-231 breast cancer cell lines. Among the cyclohexanone series, compound 4 exhibited potential cytotoxicity (IC50 = 11.04±2.80, 6.50±01.80, 8.70±3.10 and 2.30±1.60) against four proposed cancer cell lines, respectively. In addition, the spectral data of (2E,6E)-2,6-bis(2-methoxybenzylidene)cyclohexanone (1) was reported for the first time. Curcuminoids with diferuloyl (4-hydroxy-3-methoxycinnamoyl) moiety with mono carbonyl group exhibited potential cytotoxic properties.